Relationship between isokinetic strength parameters and soccer throw-in performance - Cerrah, A. O.; Gungor, E. O.; Yilmaz, I. (Research Quarterly for Exercise and Sport, 2011)
The aim of the current study was to determine ball velocity and throwing distance in standing and running throw-in techniques and to correlate these performances with isokinetic torques of the elbow, shoulder, and trunk extensors and flexors. Fourteen male amateur soccer players (M age = 22.93 years, SD = 2.27; M training status = 11.64 years, SD = 4.16), volunteered to participate the study. Isokinetic (consentric/consentric) tests were measured at 60 and 180°s-1 angular velocities for the elbow and shoulder, and 30 and 120°/s angular velocities for the trunk. Ball velocities were analyzed by radar gun, and the throwing distance was measured regarding throw-in performance. An unpaired t test was used to analyze ball velocity and throwing distance differences between two different throwing techniques. Pearson correlations were used to clarify the relationship between isokinetic strength values and ball velocities and distance that occur during the two throwing techniques. There were no statistical significant differences regarding throwing velocity and distance between the two throw-in techniques. Although the isokinetic values and throwing velocities did not correlate with each other, there was a positive correlation between standing throw-in distance with the elbow (nondominant flexion in 60 and 180°/s), shoulder (dominant flexion-extension in 60 and 180°/s, nondominant extension in 60 and 180°/s), and trunk (flexion in 30 and 120°/s). The only correlation between running throw-in and throwing distance occurred in the shoulder (dominant extension in 60°/s) and trunk (flexion in 30°/s). In conclusion, the isokinetic strength values regarding the upper extremity is a strong factor that describes standing throw-in performance. However, it is not highly correlated with the running throw-in performance in soccer.